PENGARUH RISIKO, RETURN, DAN PEREKONOMIAN INDONESIA TERHADAP KEPUTUSAN BERINVESTASI PADA ERA DISRUPTIF COVID-19 - Lutfi Damayanti; Maslichah Maslichah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study aims to determine the effect of: (1) risk (2) return (3) the Indonesian economy on investment decisions in the disruptive era of Covid-19. This type of research is descriptive associative. The data in this study are primary data obtained from distributing questionnaires and measured using a Likert scale. The population in this study were students of the 2018 of Faculty Economics and Business, University of Islam Malang. The sample in this study was 151 respondents who were determined by the Slovin formula and purposive sampling method. The data analysis technique used is multiple linear aggression using SPSS version 16. The results of this study indicate that risk, return, and the Indonesian economy simultaneously have a significant effect on investment decisions in the Covid-19 disruptive era, risk has a significant effect on investment decisions in the Covid-19 disruptive era. -19, returns have a significant effect on investment decisions in the disruptive era of Covid-19, the Indonesian economy has a significant effect on investment decisions in the disruptive era of Covid-19.Keywords : Risk, Return, Indonesian Economic, Investment Decision, Covid-19.